PODA NA LIMA SEBAGAI KONSEP LITERASI MEDIA DALAM MEMFILTERISASI BERITA HOAX - Barkah Hadamean Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2018)
The focus of this research is the understanding of lecturers and students about poda na lima of keep your soul clean and media literacy in filtering the news circulating in online media with the concept of poda na lima which focused on the concept of local wisdom with regional philosophical principles, namely paias rohamu (cleansing your soul) in students and lecturers of the Da'wah and Communication Faculty of IAIN Padangsidimpuan. The purpose of this study was to find out about the understanding and efforts of lecturers and students about the poda na lima of keep your soul clean as a form of the concept of media literacy in filtering hoax news. The type of research used by researchers is qualitative with the subject of this research carried out by random sampling with the instruments used in data collection, as a whole data collected through interviews as the main technique of the research, then strengthened by and documentation and observation. The results of the study show that the understanding of lecturers and students about the poda na lima of keep your soul clean as a form of media literacy concept is not materially raised but rather the content value of the five pillars of your spirit. The efforts of lecturers and students to instill the five pillars of keep your soul clean as a form of media literacy filtering hoax news is where the lecturer strives to provide an understanding of self-concept according to the subject area of the student through classroom learning. Producing messages as part of message creativity is the ability of someone to arrange messages or ideas with words, sounds, or images effectively in accordance with the principles of communication science